Immunosensor fabrication methods: A scoping review - Ajinugroho, Fajar; Abuzairi, Tomy; Fauziyah, Siti (JHeS (Journal of Health Studies), 2023)
Various methods of establishing a diagnosis, especially for initial diagnosis, have been widely developed, such as Rapid Diagnostic Test (RDT), Enzyme-linked immunosorbent assay (ELISA), and polymerase chain reaction (PCR). However, those tools have several different limitations in each tool. The limitations of this tool include a fairly high error rate and the need for complex tools. The work can only be used by special personnel and a long processing time. Immunosensors are tools that can be used as an alternative. Immunosensor is a sensor used to detect specific immune reactions between antibodies and targets in the form of antigens and can detect interactions between analyte targets and antibodies from changes in electrochemical signal, sot the examination time is relatively faster. This scoping review aims to review each immunosensor fabrication parameter. The results proved that each analyte has a different characterization and is very diverse. So it is necessary to select the right parameters (electrode type, immunoassay configuration, electrode modification, receptor immobilization, and electrochemical characterization). The linear range and detection limit are also important parameters that can be developed so that very limited analyte concentrations in the sample can be detected. It is necessary to review fabrication methods to improve the stability of immunosensors so that the ligands contained in the immunosensor electrodes can last a long time to be able to carry out mass production.